Performance Enhancement of a UWB Antenna Using Backing Cavity for Improved Wireless Communication Systems - Mohamad, Sarah Yasmin (2017)
Ultra Wideband (UWB) is a wireless technology for transmission of massive amounts of data over a wide frequency band using short-pulses with very low power spectral density. In 2002, FCC authorized a frequency allocation in the range of 3.1–10.6 GHz with a maximum transmitted power of -41.3 dBm/MHz for UWB commercial use. Certain applications require unidirectional radiation and thus, antennas are usually backed by either a cavity absorber or a conducting plane reflector. However, the use of absorber will decrease the efficiency to only 50%, while the metal reflector is restricted with a quarter wavelength separation between the reflector and antenna for maximum performance. The objectives of this project is to enhance the performance of wideband antennas for several communication applications which exhibit good radiation patterns with high gain and front-to-back ratio, provide acceptable impedance, with a compact and lightweight structure. The geometrical design of the antennas will be studied and the simulation/design of the antenna will be executed using CST Microwave Studio® (CST MWS). These wideband antennas can be used for military applications such as avionics and microwave direction-finding systems, CubeSat, 5G technologies and other wireless communications e.g. WLAN, WiMAX and Bluetooth, which will be a significant contribution for Malaysia in enhancing its wireless communication.